2007
DOI: 10.1016/j.virol.2007.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of the herpes simplex virus type 1 tegument protein VP22 into the virus particle is independent of interaction with VP16

Abstract: Herpes simplex virus type 1 (HSV-1) virions contain a proteinaceous layer termed the tegument that lies between the nucleocapsid and viral envelope. The mechanisms underlying tegumentation remain largely undefined for all herpesviruses. Using glutathione S-transferase (GST) pulldowns and coimmunoprecipitation studies, we have identified a domain of the tegument protein VP22 that facilitates interaction with VP16. This region of VP22 (residues 165-225) overlaps the glycoprotein E (gE) binding domain of VP22 (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 44 publications
3
51
0
1
Order By: Relevance
“…While GFP alone showed no binding activity to any of the fusion proteins, GFP-VP22 interacted efficiently with GST-gE and GST-VP16 but not GST alone (Fig. 2C), as described previously by others (32,33). Interestingly, GFP-22 also bound, but more weakly, to the C-terminal tail of gM.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…While GFP alone showed no binding activity to any of the fusion proteins, GFP-VP22 interacted efficiently with GST-gE and GST-VP16 but not GST alone (Fig. 2C), as described previously by others (32,33). Interestingly, GFP-22 also bound, but more weakly, to the C-terminal tail of gM.…”
Section: Resultssupporting
confidence: 84%
“…HSV-1 VP22 has been reported to have a number of virus binding partners, namely, VP16, gE, and gD (4,13,19,32,33). In addition, PRV VP22 has been shown to interact with the cytoplasmic tail of gM (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that pUL49 interacts with the cytoplasmic tails of HSV-1 gE, gD and envelope protein pUS9 (Chi et al, 2005;Farnsworth et al, 2007a;O'Regan et al, 2007). In PrV, interactions of pUL49 with the cytoplasmic tail of both gE and gM were identified (Fuchs et al, 2002b).…”
Section: Secondary Envelopmentmentioning
confidence: 99%
“…In PrV, interactions of pUL49 with the cytoplasmic tail of both gE and gM were identified (Fuchs et al, 2002b). Furthermore, for both HSV-1 and PrV, gE or gM is sufficient for recruitment of pUL49 into virions through a direct interaction (Fuchs et al, 2002b;Michael et al, 2006;O'Regan et al, 2007;Stylianou et al, 2009).…”
Section: Secondary Envelopmentmentioning
confidence: 99%